Tahapan dan Tantangan Pembangunan Literasi Digital di Era Transformasi Digital - Najirah Umar; Andi Asyhary J. Arsyad (Journal of Digital Literacy and Volunteering, 2025)
Digital literacy is vital in today's information age, affecting various aspects of life, including education, employment, and social interaction. The study explores the stages of digital literacy development and its implications for individuals and organizations. The research aims to identify key factors that affect digital literacy and propose strategies to enhance it. Research highlights the importance of access to digital tools, training, and sustainable learning in promoting digital literacy. The study concludes that targeted interventions and supportive policies are essential for the development of effective digital literacy, which ultimately contributes to personal and social progress.